2010
DOI: 10.1002/adma.200902658
|View full text |Cite
|
Sign up to set email alerts
|

Testing Metal‐Oxide Nanomaterials for Human Safety

Abstract: Nanomaterials can display distinct biological effects compared with bulk materials of the same chemical composition. The physico-chemical characterization of nanomaterials and their interaction with biological media are essential for reliable studies and are reviewed here with a focus on widely used metal oxide and carbon nanomaterials. Available rat inhalation and cell culture studies compared to original results suggest that hazard potential is not determined by a single physico-chemical property but instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
246
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(257 citation statements)
references
References 172 publications
3
246
1
7
Order By: Relevance
“…Furthermore, a high-dosed spray was modeled based on doses and particle size distributions reported for some consumer sprays (Quadros & Marr, 2011) as well as high dose experiments on rats (Landsiedel et al, 2010. For the NPs a dose equivalent to 1 Â 10 8 particles/cm 3 of the respective NP at an agglomerated state of CMD ¼ 250 nm and a GSD ¼ 2.0 (corresponding to 2.476 mm MMAD) was assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a high-dosed spray was modeled based on doses and particle size distributions reported for some consumer sprays (Quadros & Marr, 2011) as well as high dose experiments on rats (Landsiedel et al, 2010. For the NPs a dose equivalent to 1 Â 10 8 particles/cm 3 of the respective NP at an agglomerated state of CMD ¼ 250 nm and a GSD ¼ 2.0 (corresponding to 2.476 mm MMAD) was assumed.…”
Section: Resultsmentioning
confidence: 99%
“…TEM results revealed that serum in the culture medium contributed substantially to particle dispersion and allowed particles to enter the human lung cells. In serum-free medium, MNPs underwent rapid aggregation apparently because of a high ionic strength of culture medium [30] and no MNPs were found inside the cells. A rapid agglomeration of polyvinyl alcohol/vinyl amine coated magnetite nanoparticles in serum-free medium have reported also Petri-Fink et al [31].…”
Section: Discussionmentioning
confidence: 99%
“…This conformity suggests that serum proteins adsorbed onto the particle surface, with the result that protein-coated ZnO particles appeared electrostatically to be like the free serum proteins. Such zeta potential values of protein-covered particles in physiological media are often found and seem to be particleindependent [23,45,46].…”
Section: Discussionmentioning
confidence: 99%